2011
DOI: 10.1192/bjp.bp.110.078741
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bipolar disorder in children and adolescents with attention-deficit hyperactivity disorder

Abstract: BackgroundSome research suggests that children with attention-deficit hyperactivity disorder (ADHD) have a higher than expected risk of bipolar affective disorder. No study has examined the prevalence of bipolar disorder in a UK sample of children with ADHD.AimsTo examine the prevalence of bipolar disorder in children diagnosed with ADHD or hyperkinetic disorder.MethodPsychopathology symptoms and diagnoses of bipolar disorder were assessed in 200 young people with ADHD (170 male, 30 female; age 6–18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This question arose in part from observations of a high rate of "manic-like" symptoms in clinical samples of children with ADHD (10, 11), a high rate of ADHD in clinically referred children with ultra-rapid cycling bipolar disorder (12), and a high rate of comorbidity in some cross-sectional studies of children of bipolar parents (13). However, the diagnosis of mania in clinically referred pediatric samples is a point of debate (14), and elevated rates of comorbid ADHD and bipolar disorder are not consistently found in pediatric clinical (15) or high-risk study cohorts (16,17).…”
mentioning
confidence: 96%
“…This question arose in part from observations of a high rate of "manic-like" symptoms in clinical samples of children with ADHD (10, 11), a high rate of ADHD in clinically referred children with ultra-rapid cycling bipolar disorder (12), and a high rate of comorbidity in some cross-sectional studies of children of bipolar parents (13). However, the diagnosis of mania in clinically referred pediatric samples is a point of debate (14), and elevated rates of comorbid ADHD and bipolar disorder are not consistently found in pediatric clinical (15) or high-risk study cohorts (16,17).…”
mentioning
confidence: 96%
“…For example, using a nationwide psychiatric case register in Denmark covering a background population of 5.1 million inhabitants, 39 children (23 boys, 16 girls) were identified has having the diagnosis of manic-depressive psychosis between 1970 and 1986 before the age of 15 (Thomsen et al 1992). In addition, no cases of mania were found in a British clinic survey of 2500 children aged 10 and under (Harrington and Myatt 2003) and only one child met diagnostic criteria for both ICD-10 hypomania and DSM-IV bipolar disorder NOS in a UK sample of 200 young people with ADHD (6-18 years, mean age 11.15) (Hassan et al 2011). A recent meta-analysis re-examined prevalence rates of paediatric bipolar disorder in epidemiological samples (Van Meter et al 2019).…”
Section: Cross-national Differencesmentioning
confidence: 99%
“…Rates of PBD in children with ADHD vary widely depending on the sample and which assessment approach is used (Pataki & Carlson, 2013). Specifically, a number of reviewers have pointed out that differences in methodologies influence rates of PBD in ADHD samples and rates of ADHD in PBD samples (Carlson, 2011; Galanter & Leibenluft, 2008; Hassan, Agha, Langley, & Thapar, 2011; Pataki & Carlson, 2013). Serrano, Ezpeleta, and Castro-Fornieles (2013) found that 8% of an ADHD sample met criteria for PBD and 6% for BD–not otherwise specified (BD-NOS).…”
Section: Introductionmentioning
confidence: 99%